Epilepsy duration is an independent factor for electrocardiographic changes in pediatric epilepsy. Issue 3 (19th July 2021) - Chan, See Wai; Dervan, Leslie A.; Watson, Robert Scott; Anderson, Anne E.; Lai, Yi‐Chen
Abstract: Objective: Cardiac alterations represent a potential epilepsy‐associated comorbidity. Whether cardiac changes occur as a function of epilepsy duration is not well understood. We sought to evaluate whether cardiac alterations represented a time‐dependent phenomenon in pediatric epilepsy. Methods: We retrospectively followed pediatric epilepsy patients without preexisting cardiac conditions or ion channelopathies who had history of pediatric intensive care unit admission for convulsive seizures or status epilepticus between 4/2014 and 7/2017. All available 12‐lead electrocardiograms (ECGs) from these patients between 1/2006 and 5/2019 were included. We examined ECG studies for changes in rhythm; PR, QRS, or corrected QT intervals; QRS axis or morphology; ST segment; or T wave. Data were analyzed using multivariable models containing covariates associated with ECG changes or epilepsy duration from the univariate analyses. Results: 127 children with 323 ECGs were included in the analyses. The median epilepsy duration was 3.9 years (IQR 1.3‐8.4 years) at the time of an ECG study and a median of 2 ECGs (IQR 1‐3) per subject. The clinical encounters associated with ECGs ranged from well‐child visits to status epilepticus. We observed changes in 171 ECGs (53%), with 83 children (65%) had at least 1 ECG with alterations. In a multivariable logistic regression model adjusting for potentially confounding variables and accounting for clustering by patient, epilepsy duration was independently associated with altered ECGs for each year of epilepsy (OR: 1.1, 95% CI: 1.0‐1.2, P = .002). Extrapolating from this model, children with epilepsy durations of 10 and 15 years had 2.9 and 4.9 times the odds of having ECG changes, respectively. Significance: Cardiac alterations may become more common with increasing epilepsy duration in select pediatric epilepsy patients. Future studies are needed to determine the potential clinical implications and the generalizability of these observations.